Time to live: Writing war and empire in the South Caucasus - Sutcliffe, Benjamin (Studia Rossica Posnaniensia, 2025)
In 2003 the Georgian and Abkhaz writers Guram Odisharia and Daur Nachkebia published the literary collection Time to live (Vremia zhit’), which includes eighteen authors from the South Caucasus depicting the late 1980s-1990s armed conflicts in Abkhazia, Georgia, Nagorno-Karabakh, and South Ossetia. Most of their works were translated into Russian for the book. This volume tried to promote peace and intercultural dialog within the region. However, in doing so it unintentionally illuminated the Russian language’s role as agent of oppression as well as intermediary. Russophonia (writing in Russian outside the Russian Federation) and problems of postcoloniality are central to the collection’s portrayal of the South Caucasus. The article draws on criticism by Gayatri Spivak, Tamar Koplatadze, Naomi Caffee, and others, as well as research conducted in Georgia in 2018 and 2023.